The Helium and Carbon Isotope Characteristics of the Andean Convergent Margin - Barry, P. H.; De Moor, J. M.; Chiodi, A.; Aguilera, F.; Hudak, M. R.; Bekaert, D. V.; Turner, S. J.; Curtice, J.; Seltzer, A. M.; Jessen, G. L.; Osses, E.; Blamey, J. M.; et al. (Frontiers in Earth Science, 2022)
Subduction zones represent the interface between Earth’s interior (crust and mantle) and exterior (atmosphere and oceans), where carbon and other volatiles are actively cycled between Earth reservoirs by plate tectonics. Here, we report helium isotope and abundance data for 42 deeply-sourced fluid and gas samples from the CVZ and SVZ. He isotopes from the CVZ backarc range from 0.1 to 2.6 RA (n = 23), with the highest value in the Puna and the lowest in the Sub-Andean foreland fold-and-thrust belt. Atmosphere-corrected He isotopes from the SVZ range from 0.7 to 5.0 RA (n = 19). Taken together, these data reveal a clear southeastward increase in 3He/4He, with the highest values (in the SVZ) falling below the nominal range of values associated with pure upper mantle He (8 ± 1 RA), approaching the mean He isotope value for arc gases of (5.4 ± 1.9 RA). Notably, the lowest values are found in the CVZ, suggesting more significant crustal inputs (i.e., assimilation of 4He) to the helium budget. The crustal thickness in the CVZ (up to 70 km) is significantly thicker than in the SVZ, where it is just ~40 km. We suggest that crustal thickness exerts a primary control on the extent of fluid-crust interaction, as helium and other volatiles rise through the upper plate in the ACM. We also report carbon isotopes from (n = 11) sites in the CVZ, where δ13C varies between -15.3 and -1.2 ‰ (vs. Vienna Pee Dee Belemnite (VPDB)) and CO2/3He values that vary by over 2 orders of magnitude (6.9 × 108 to 1.7 × 1011). In the SVZ, carbon isotope ratios are also reported from 13 sites and vary between -17.2 and -4.1 ‰. CO2/3He values vary by over 4 orders of magnitude (4.7 × 107 to 1.7 × 1012). Low δ13C and CO2/3He values are consistent with CO2 removal (e.g., calcite precipitation) in shallow hydrothermal systems. Carbon isotope fractionation modeling suggests that calcite precipitation occurs at temperatures coincident with the upper temperature limit for life (122 °C), suggesting that biology may play a role in C-He systematics of tectonic fluid emissions.